P1713A CASE OF DEVASTATING BARIATRIC SURGERY-RELATED ACUTE OXALATE NEPHROPATHY FIRST DIAGNOSED AFTER KIDNEY TRANSPLANTATION. (6th June 2020) - Santarsia, Francesca; Gandolfini, Ilaria; Delsante, Marco; Palmisano, Alessandra; Peyronel, Francesco; Sabatino, Alice; Regolisti, Giuseppe; Fiaccadori, Enrico; Maggiore, Umberto
Abstract: Background and Aims: Despite the obvious efficacy in achieving weight loss, traditional malabsorptive procedures (intestinal by-pass) used for the treatment of obesity, may be associated with enteric oxaluria. Enteric oxaluria, by causing calcium-oxalate stones and nephrocalcinosis, represents an under-recognized cause of end-stage kidney disease in patients with history of intestinal by-pass. Herein, we describe a patient with a long-standing history of intestinal by-pass who developed a devastating acute oxalate nephropathy first diagnosed after kidney transplantation. Method: A white female aged 50, who started hemodialysis one year earlier because of tubule-interstitial nephritis on a kidney biopsy, and who had history of recurrent kidney stones (calcium oxalate), underwent urgent deceased-donor kidney transplantation because of exhausted vascular access for hemodialysis (tunneled CVC right giugular vein as the last resort). She had received intestinal by-pass surgery 20 yrs earlier, and had a pacemaker implantation in the left sublavian vein for AV block two years earlier. She was highly sensitized because of blood transfusions at the time of surgery. Results: After transplantation, graft function had immediate recovery, serum creatinine decreasing to 2.0mg/dL (117 mmol/L) on post-operative day (POD) 3. Shortly after, serum creatinine started rising until it reached 4.0mg/dL (354mmol/L) on POD 5. Three graft biopsies (performed on POD 6, 9 and 15 post-transplant) revealed acute oxalate nephropathy ( Figure1-2: large oxalate crystals on fresh unfixed core of kidney tissue analyzed under bright field microscope using polarized light) with no sign of rejection. Serial monitoring of Luminex SAB did not reveal circulating anti-HLA donor specific antibodies. Fundus examination revealed two tiny mono-lateral retinal oxalate deposits, whereas bone biopsy did not reveal oxalate accumulation. Plasma oxalate levels were 43 mmol/L on POD 10 were urinary oxalate excretion was 29mg /day on POD 14. The patient slowly progressed to end-stage kidney disease 2-month post-transplantation despite daily high flux dialysis since POD 7, fat-free and oxalate-free diet, oral potassium and high dose pyridoxine supplements. Conclusion: Patients on chronic dialysis with a previous history of bariatric surgery via intestinal by-pass may have oxalate nephropathy caused by enteric oxaluria as unknown primary renal disease. The disease may recur shortly after transplantation despite the adoption of prompt aggressive treatment for oxalate removal.